Kepemimpinan Kepala Sekolah dalam Pengembangan Manajemen SDN Sendangmulyo 02 - Andriastuti Andriastuti; Husni Wakhyudin; Suherni Suherni (Journal on Education, 2023)
Principals are leaders who have a dominant role in managing education in schools. The role of the principal is primarily to manage the school including the process of planning, organizing, directing and controlling resources. In the organizational structure. So the policy set by the principal is the final decision. The purpose of this study was to determine the principal’s leadership in developing school management of SDN Sendangmulyo 02 Semarang. This research uses a qualitative approach with description method. Data collection through observation, interview and documentation. Data analysis used triangulation of sources, methods and theoretical studies. It is known that the implementation of education management at SDN Sendangmulyo 02 Semarang is guided and refers to the national standards of education. The implementation of management includes student management, curriculum management, human resource management, facilities and infrastructure management, budget management, information system management, and management of management runs smoothly and orderly. School management is carried out with coordination between principals, teachers, education personnel and school committees to support everything related to learning, needs in learning, school activities.